Wasathiyyah Islam Perspective K. H. Ahmad Hasyim Muzadi - Habiba Darajat; Muhamad Arif (Institut Attanwir Bojonegoro, 2024)
Washathiyyah Islam is a middle-line (moderate) Islam that is appropriate to be implemented in Indonesia. A harmonious combination of state and religion is the key to the process of living a safe and peaceful life. As the view of Washathiyyah Islam explained by KH. Ahmad Hasyim Muzadi can be used as a basis for a friendly Islamic religion (rahmatan lil alamin), the aim of this research is to analyze the Islamic concept of washatiyyah from KH's perspective. Ahmad Hasyim Muzadi. The research method used is library research, which is combined with the process of analyzing data through content analysis from Elo. The research results show that the concept of moderate Islam, as explained by KH. Ahmad Hasyim Muzadi, is a simple concept but has great potential to be implemented in people's lives. The first concept is Islamic religious ideology that is not extreme or excessive (ghulluw) because it can harm or even destroy Islam. Second, the scope of multiculturalism and multireligion starts with maintaining brotherhood between religions, getting to know each other, and acculturating culture and Islam, which is rahmatan lil alamin. Third, the integration of Islamic education that is Islamic and adheres to Pancasila, starting with maintaining democracy, love of the homeland, and istiqomah.